The Effect of Sun Protection Education Given to Nursing Students on the Level of their Knowledge about Skin Cancer and Sun: A Randomized Controlled Study - Asli Akdeniz Kudubes (Professor Despina Sapountzi-Krepia, 2024)
The Effect of Sun Protection Education Given to Nursing Students on the Level of their Knowledge about Skin Cancer and Sun: A Randomized Controlled Study